T-B cell interaction inhibits spontaneous apoptosis of mature lymphocytes in Bcl-2-deficient mice. - Nakayama, K; Nakayama, K; Dustin, L; Loh, D (1995)
Bcl-2 expression is tightly regulated during lymphocyte development. Mature lymphocytes in Bcl-2-deficient mice show accelerated spontaneous apoptosis in vivo and in vitro. Stimulation of Bcl-2-deficient lymphocytes by anti-CD3 antibody inhibited the spontaneous apoptosis not only in T cells but also in B cells. The rescue of B cells was dependent on the presence of T cells, mainly through CD40L and interleukin (IL)-4. Furthermore, we generated Bcl-2-deficient mice transgenic for a T cell receptor or an immunoglobulin, both specific for chicken ovalbumin, to test for antigen-specific T-B cell interaction in the inhibition of the spontaneous apoptosis. The initial T cell activation by antigenic peptides presented by B cells suppressed apoptosis in T cells. Subsequently, T cells expressed CD40L and released ILs, leading to the protection of B cells from spontaneous apoptosis. These results suggest that the antiapoptotic signaling via CD40 or IL-4 may be largely independent of Bcl-2. Engagement of the Ig alone was not sufficient for the inhibition of B cell apoptosis. Thus, the physiological role of Bcl-2 in mature lymphocytes may be to protect cells from spontaneous apoptosis and to extend their lifespans to increase the opportunity for T cells and B cells to interact with each other and specific antigens in secondary lymphoid tissues. Bcl-2, however, appears to be dispensable for survival once mature lymphocytes are activated by antigen-specific T-B cell collaboration.